MODERN COMPUTER PROCESSOR STRUCTURE - Škapars, Arturs; Laduševs, Aigars; Grabusts, Pēteris (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2018)
This article is about computer processor structure, that has improved over time and is still evolving. The goal of this work is to delve into specifics of computer processors and the logic they obey. This paper will overlook parts of modern computer processor structure to understand how they work.